The Impact of Globalization on the Dynamics of the Constitutional Law System in Indonesia: An Analytical Review - Hidayat, Anwar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Globalization has become a phenomenon that dominates social, economic and political developments in various countries, including Indonesia. In the context of constitutional law, globalization has given rise to various challenges and significant changes in legal regulations and practices in Indonesia. This research aims to analyze the influence of globalization on the constitutional law system in Indonesia. This research uses a normative legal approach through a regulatory and legal approach that is in accordance with the research theme. The research results show that globalization has a significant impact on the constitutional law system in Indonesia. Analysis of the adoption of international legal principles, changes in government institutions, shifts in power structures, developments in technology and communications, as well as the challenges and opportunities faced by Indonesia illustrates the complexity of the interaction between globalization and constitutional law. By understanding these dynamics, this research highlights the need to adapt the constitutional law system in Indonesia to respond to the challenges of globalization by maintaining state sovereignty, strengthening public participation, and ensuring the protection of national interests while taking advantage of global integration opportunities for sustainable development.